Using art th erapy in penitentiary rehabilitation - Katarzyna Wioleta Korona (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
iIntroduction. The aim of the proposed paper is to draw attention to the possibility of using art therapy in social rehabilitation with socially maladjusted people, with particular emphasis on penitentiary rehabilitation. description of the state of knowledge. Art-therapy effects will be presented from the perspective of penitentiary and rehabilitation practice. The author will refer problems and opportunities associated with the choice of artetherapy as the main method of conducting interactions with prisoners who have been sentenced to long term deprivation of liberty. Summary. In the last part of the paper, reflections will be included, taking into account the experience from the implementation of proprietary programs in prisons.